Anthropometric percentiles of preterm newborns with low birth weight and very low birth weight, participants of a kangaroo mother program in Santiago de Cali, Colombia - Meneses, Sara (2023)
Objective: The kangaroo mother method provides care and attention practices for preterm or low birth weight newborns that favor their development in the postnatal stage. This research aims to establish the distribution of anthropometric percentiles of height, weight, and head circumference (HC) of newborns in a follow-up program for preterm, low birth weight (LBW), and very low birth weight (VLBW) infants in the city of Santiago de Cali from 2016 to 2018. Materials and methods: The information was obtained from an institutional database of a Mother Alpha Kangaroo House Program in the city of Santiago de Cali, Colombia. Subjects who attended for follow-up at least eight times and had complete data on age, weight, height, and HC were included. Children who withdrew from the program before the first year of life and newborns with conditions that could bias anthropometric development during the first year of life were excluded. Statistical analyses were performed by sex and according to birth weight; VLBW (<1500 g) and LBW (1,500 - 2,500 g). Percentile modeling was done in R with the GAMLSS statistical package. Results: Of 3689 records in the database, 692 subjects were selected. The sample was evenly distributed by sex, with 50.4% boys and 49.6% girls. Sixty-two percent of the subjects had LBW and 38% had VLBW. The group of newborns with LBW had higher birth weight and HC than girls (p<0.05), and in the VLBW group, girls had lower HC than boys (p<0.05). The percentiles and smoothed reference curves for the variables studied showed progressive gain during the first 12 months. Conclusions: Percentiles and modeled curves are a tool for monitoring, follow-up, and objective comparison of the development and anthropometric growth of preterm newborns who have participated in the kangaroo mother method.